The Utility of Wealth and the Utility of Windfalls - Flemming, J. S. (Review of Economic Studies, 1969)
Journal Article The Utility of Wealth and the Utility of Windfalls Get access J. S. Flemming J. S. Flemming Nuffield College, Oxford Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 36, Issue 1, January 1969, Pages 55–66, https://doi.org/10.2307/2296342 Published: 01 January 1969 Article history Received: 23 October 1967 Revision received: 08 July 1968 Published: 01 January 1969